2014
DOI: 10.2113/gsjfr.44.4.341
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Acidification Not Likely to Affect the Survival and Fitness of Two Temperate Benthic Foraminiferal Species: Results From Culture Experiments

Abstract: Specimens of Bolivina argentea and Bulimina marginata, two widely distributed temperate benthic foraminiferal species, were cultured at constant temperature and controlled pCO 2 (ambient, 1000 ppmv, and 2000 ppmv) for six weeks to assess the effect of elevated atmospheric CO 2 concentrations on survival and fitness using Adenosine Triphosphate (ATP) analyses and on shell microfabric using high-resolution SEM and image analysis. To characterize the carbonate chemistry of the incubation seawater, total alkalinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 85 publications
(3 reference statements)
2
8
0
Order By: Relevance
“…Precipitation of shells is enhanced by photosynthesis during daylight hours. Our experiment, as well as those of Dissard et al (2010), McIntyre-Wressnig et al (2014), and others, indicates that, once precipitated, shell calcite is relatively protected from dissolution while the foraminifer is alive. While lower pH conditions will require greater energy expenditure to precipitate CaCO 3 , photosynthesis by diatom symbionts may be enhanced by higher pCO 2 (e.g., Johnson et al, 2013).…”
Section: Implications: Past and Futuresupporting
confidence: 80%
See 1 more Smart Citation
“…Precipitation of shells is enhanced by photosynthesis during daylight hours. Our experiment, as well as those of Dissard et al (2010), McIntyre-Wressnig et al (2014), and others, indicates that, once precipitated, shell calcite is relatively protected from dissolution while the foraminifer is alive. While lower pH conditions will require greater energy expenditure to precipitate CaCO 3 , photosynthesis by diatom symbionts may be enhanced by higher pCO 2 (e.g., Johnson et al, 2013).…”
Section: Implications: Past and Futuresupporting
confidence: 80%
“…gibbosa exposed in culture to 2000 ppmv pCO 2 for six weeks, while finding that neither survival nor cellular energy levels were affected. McIntyre-Wressnig et al (2014) similarly found that two common temperate benthic species showed no direct effect of high pCO 2 on survival or fitness even when seawater was undersaturated with respect to calcite.…”
Section: Effects Of Temperature and Phmentioning
confidence: 90%
“…A direct comparison of foraminiferal survival rates can be made with the studies of McIntyre-Wressnig et al (2013, although survival was determined in those studies using a different method (ATP analysis). After six weeks, survival rates for Bulimina marginata, also collected from the Mud Patch, were ~73-89% among control populations and 68-82% in populations exposed to enhanced pCO 2 (1000 and 2000 ppmv; McIntyre-Wressnig et al, 2014). These survival rates for B. marginata are similar to those observed in this study for G. turgida (60-90%).…”
Section: Survivorshipsupporting
confidence: 83%
“…Tests from a previous study that used the Biospherix CO2 system showed that the atmosphere and seawater are in equilibrium within 40 h after introduction to the controlled atmosphere within the chamber (McIntyre-Wressnig et al, 2014). All treatments were fed weekly with 1 ml of a concentrated mixture of live Dunaliella tertiotecta Butcher and Isochrysis galbana Parke.…”
Section: Sedimentmentioning
confidence: 99%
“…The use of CTG in foraminiferal laboratory experiments, such as bioassays, is less established. McIntyre-Wressnig et al (2014) employed it to identify live foraminifers for experiments and Pucci et al (2009) used it to identify surviving individuals following experimental treatments. The primary objective of our study was to determine if CTG could be used to distinguish live from dead A. gibbosa in laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%